Neomycin Sulfate Emulgel Formulation With Avocado Seed Starch As Gelling Agent - Vinny Valentina Kaitu; Hosea Edy; Karlah Lifie Riani Mansauda (PHARMACON, 2023)
Emulgel is a combined form of emulsion and gel dosage that is stable with the addition of a gelling agent. Starch can also be used as an additive in gel dosage as a gelling agent. This study aims to formulate a modification of acetylation of avocado seed starch as a gelling agent for neomycin sulfate emulgel preparations. Avocado seed starch was modified by the acetylation method. The emulgel formula was made with a concentration of avocado seed starch gelling agent of 2%, 4%, 6%, and 8%. The physical evaluation of neomycin sulfate emulgel preparations included organoleptic tests, homogeneity tests, pH tests, adhesion tests, and dispersion tests. The results showed that acetylated modified avocado seed starch can be used as a gelling agent in emulgel preparations and that all neomycin sulfate emulgel preparation formulas met the requirements for physical evaluation of the preparation.